2023
DOI: 10.3390/ijerph20031724
|View full text |Cite
|
Sign up to set email alerts
|

Application of Deep Learning Model in the Sonographic Diagnosis of Uterine Adenomyosis

Abstract: Background: This study aims to evaluate the diagnostic performance of Deep Learning (DL) machine for the detection of adenomyosis on uterine ultrasonographic images and compare it to intermediate ultrasound skilled trainees. Methods: Prospective observational study were conducted between 1 and 30 April 2022. Transvaginal ultrasound (TVUS) diagnosis of adenomyosis was investigated by an experienced sonographer on 100 fertile-age patients. Videoclips of the uterine corpus were recorded and sequential ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Further fields of applications were found in the process of this literature review. In total, 11 articles were summarized in this section, including the topics of endometriosis [216,217], premature ovarian failure [218,219], uterine fibroids [220,221], follicle tracking [222,223], and ectopic pregnancies [224,225]. Another study addressed the issue of poor image quality in 3D US images due to data processing and showed that AI image enhancement methods could produce increased 3D image quality with user-preferential flexibility in both gynecological and obstetric US images [226].…”
Section: Other Applications In Gynecologymentioning
confidence: 99%
See 2 more Smart Citations
“…Further fields of applications were found in the process of this literature review. In total, 11 articles were summarized in this section, including the topics of endometriosis [216,217], premature ovarian failure [218,219], uterine fibroids [220,221], follicle tracking [222,223], and ectopic pregnancies [224,225]. Another study addressed the issue of poor image quality in 3D US images due to data processing and showed that AI image enhancement methods could produce increased 3D image quality with user-preferential flexibility in both gynecological and obstetric US images [226].…”
Section: Other Applications In Gynecologymentioning
confidence: 99%
“…Two included articles discussed the sensitive topic of endometriosis, which can be problematic for both physician and patient due to complex clinical management and impaired quality of life in affected women [216,217]. Both studies had the usage of transvaginal 2D US videos and the missing histopathological or surgical confirmation in common, but focused on two different manifestations of endometriosis.…”
Section: Endometriosismentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most frequent gynecological disorders affecting women of childbearing age is UF [26]. Some of the signs of these benign tumors of the uterine muscle are painful periods, inability to conceive, and heavy monthly bleeding [27].…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, a study [17] achieved 96.4% accuracy using the VGG16 CNN model as a pre-trained feature extractor, which was trained on their ultrasound images dataset. To automate UF detection from an ultrasound image, a DCNN architecture was developed in another work [26]. The suggested model extracted features from ultrasound images using a combination of convolutional, pooling, and fully connected layers.…”
Section: Related Workmentioning
confidence: 99%